Chicana Falsa Reading Flyer
Skylight Books presents Award-winning writer Michele Serros reading and discussing her book "Chicana Falsa and Other Stories of Death, Identity and Oxnard." Skylight Books in Los Feliz. n.d. Circa 1990.